#### Answer

y+3=-11(x-0)
y=-11x-3

#### Work Step by Step

y-y$_1$=m(x-x$_1$)
y-(-3)=-11(x-0)
y+3=-11(x-0)
This is point-slope form. Now isolate y to find slope-intercept form.
y+3=-11(x)-11(0)
y+3=-11x
y+3-3=-11x-3
y=-11x-3
This is slope-intercept form.

Published by
Pearson

ISBN 10:
0-13417-805-X

ISBN 13:
978-0-13417-805-9

y+3=-11(x-0)
y=-11x-3

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.